Political connections and zombie firms: The role of the 2008 stimulus plan in China - Li, Jie; Guo, Xiaowei; Huang, Bihong; Zhou, Tianhang (Journal of Financial Stability, 2024)
This paper explores the impact of political connections on zombie business in the presence of massive economic stimulus. Although a stimulus plan may substantially ease financial constraints for a politically connected firm, it distorts the firm’s decision regarding market exit. Exploiting China’s 2008 stimulus package as a semi natural experiment, we show that a firm with political connections is more likely to become a zombie following such stimulus measures. Further analysis indicates that the zombification impact of the stimulus plan is more pronounced for the firms operating in the key industries targeted by the stimulus package.